Effect of Marolo (Annona crassiflora Mart.) Pulp Flour Addition in Food Bars - Jéssyca Santos Silva; Clarissa Damiani; Edson Pablo Silva; Cristiane Rodrigues Gomes Ruffi; Eduardo Ramirez Asquieri; Thays Lorrayne Lavrinha e Silva; Eduardo Valério de Barros Vilas Boas (Journal of Food Quality)
Due to increasing consumer demand for healthy foods, attempts are being made to improve their nutritional value. Thus, there is a necessity to develop food bars enriched with dietary fiber and palatable nutritional components. The aim of this study was to evaluate the shelf life of food bars, prepared with different proportions of marolo pulp flour (20, 30, 40, and 50% replacement of oatmeal) for six-month storage, through nutritional and physical analysis, as well as sensory acceptance. The total dietary fiber content showed an average of 7.1 g·100 g−1. There was a significant increase in antioxidant activity, vitamin C, and total carotenoids content according to increasing concentration of marolo pulp flour in the food bars. In sensory evaluation, the food bar with addition of 50% marolo pulp flour showed higher averages for all evaluated attributes and was the favorite by the evaluators.